Effectiveness and safety of follitropin delta in routine clinical practice in the Nordics and Switzerland (the NORSOS study): a prospective non-interventional study - Pinborg, Anja; Sopa, Negjyp; Ekerhovd, Erling; Iliadis, Stavros I.; Kaspersen, June; Gravotta, Enrica; Quaas, Alexander (Frontiers in Endocrinology, 2025)
BackgroundFollitropin delta is the first approved human recombinant follicle-stimulating hormone treatment administered through an algorithmic individualized dosing regimen based on body weight and anti-Müllerian hormone (AMH) levels. This study assesses the effectiveness and safety profile of follitropin delta in women naïve to in vitro fertilization or intracytoplasmic sperm injection undergoing their first assisted reproductive technology cycle in a general clinical setting.Study designThis prospective observational study was conducted from August 2022 to March 2024 across 14 fertility clinics in Denmark, Norway, Sweden, and Switzerland. Consenting women with infertility (≥18 years old) receiving their first assisted reproductive technology cycle and first follitropin delta treatment were enrolled. Both fresh and frozen embryo transfers were evaluated. Follow-up continued until confirmed pregnancy outcome, early pregnancy loss, or study withdrawal. Data on follitropin delta usage, ovarian stimulation, embryo development, and safety were collected through electronic case-report forms. Patient-reported satisfaction with the follitropin delta pre-filled pen was assessed using patient questionnaires.ResultsOf the 201 women enrolled, 199 completed the study. Of these, 147 (73.9%) were aged <35 years (median 32 years). The primary reason for infertility was male factor (88/199, 44.2%). Baseline characteristics included a mean body weight of 68.9 kg, and a mean AMH baseline concentration of 21.3 pmol/L, with 130/199 (65.3%) participants having AMH concentrations >15 pmol/L. Overall, 169/199 (84.9%) participants were prescribed follitropin delta according to the calculated algorithmic dose, with a mean starting dose of 10.2 µg and a mean duration of ovarian stimulation of 9.9 days. The gonadotropin-releasing hormone antagonist protocol was used in 171/193 (88.6%) women. Almost half of the analysis population (93/194, 47.9%) achieved the algorithm-targeted response of 8–14 oocytes retrieved, and >15 oocytes were obtained in 55/194 (28.4%) women. Ongoing pregnancy rate assessed by ultrasonography 10–11 weeks after embryo transfer was 82/155 (52.9%). Ovarian hyperstimulation syndrome (all mild cases) was reported in 8/199 (4.0%) women. Almost all women (190/193, 98.4%) expressed satisfaction with the injection pen.ConclusionsThe NORSOS study (NCT05499052) provides insights into the use of follitropin delta in routine clinical practice and complements previous evidence regarding its effectiveness and safety profile.